Human rabies among the paediatric population in Bangladesh - Dey, AC; Shahidullah, M; Hossain, MA; Mannan, MA; Mitra, U (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 245-251. The abstract of this article is available on the PubMed website